Dynamical Link of Peat Fires in South Sumatra and the Climate Modes in the Indo-Pacific Region - Raden Putra; Deni Okta Lestari; Edy Sutriyono; Sabaruddin Sabaruddin; Iskhaq Iskandar (Faculty of Geography, Universitas Gadjah Mada, 2019)
Peat fire is one of the environmental disasters occurring widespread during the dry season in South Sumatra. The region has long been recognized to have extensive peatland, hence it is considered as the vulnerable areas to fire. This study employs spatial analysis to evaluate the likely linked factors causing peat fire in the study area. Two interannual climate modes such as the El Niño – Southern Oscillation and Indian Ocean Dipole were considered to have affected the area with respect to climate anomaly at the 1995-2016 periods. This phenomenon was followed by the peat fire in many areas. There appears a close linkage between the occurrence of peat fires and climate anomaly. A number of hotspots tend to occur annually during the drought season. A significant number of hotspots took place during the 2006 pIOD and 2015 El Niño events due to a significant decrease in rainfall intensities.